Effect of Lighting Schedule on the Performance of Broilers - Dhumal, Manik V.; Khutal, Ganesh P.; Kadam, Avinash S.; Lonkar, 1Vijaysinh D.; Patodkar, Vishwambhar R.; Mhase, Prashant P.; Dhaygude, Vitthal S. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Day-old commercial broiler chicks (n = 240) were randomly distributed into four treatments, each having 60 birds. Eachtreatment was further subdivided into three replicates of 20 birds each. All the groups were provided near-continuous light(23L:1D) during the initial seven days. Group A continued with near-continuous light (23L:1D) till six weeks, while Groups B, Cand D were subjected to 18L:6D, 16L:8D and 14L:10D lighting schedule, respectively, from the second week to the fifth week andsubsequently provided near-continuous light in the sixth week. The parameters studied were body weight (b.wt), weight gain (WG),feed intake (FI), feed conversion ratio (FCR), mortality, eviscerated yield (EVSY), giblet yield (GY), ready-to-cook yield (R-to-C), breastmeat yield (BY), abdominal fat weight, weight of thymus, spleen, bursa of Fabricius, H/L ratio, and leg disorder (Gait score). The resultsof the study indicated that different lighting schedules do not significantly influence b.wt, WG, FI, FCR, EVSY, GY, R-to-C, BY, H/L ratio,abdominal fat. Mortality was higher in Group A provided with near-continuous light than Group B, C, and D. The 10 hours darknessschedule significantly improved the weight of the thymus. The incidence of birds falling in painfully gait and welfare issues were lessin 6, 8, or 10 hours darkness schedule. However, its differences were non-significant.
Keywords: Broilers; Gait score; Growth, Leg disorder; Lighting schedule